Green Marketing Orientation and Gen Z Consumers: Mediation of Green Brand Awareness and Psychological Satisfaction in Sustainable Fashion - Muhamad Al Faruq Abdullah; Wenny Desty Febrian (Dinasti Publisher, 2025)
This study investigates the impact of green marketing orientation on Generation Z consumers’ behavior in sustainable fashion, focusing on the mediating roles of green brand awareness and psychological satisfaction. As environmental consciousness rises, Generation Z emerges as a pivotal segment with strong sustainable consumption values. A quantitative research method was applied using an online survey of 210 Gen Z respondents in Indonesia, the most of whom were female university students (19–23 years), familiar with sustainable fashion via digital platforms. Data were analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results indicate that green marketing orientation significantly and positively influences both green brand awareness and psychological satisfaction. These two variables, in turn, have a significant positive effect on sustainable consumer behavior. Furthermore, both mediators fully mediate the relationship between green marketing orientation and Gen Z consumer behavior. these findings highlight the importance of emotional connection and brand perception in eco-conscious fashion consumption. This research contributes to the green marketing literature and offers practical insights for sustainable fashion brands in developing targeted strategies aligned with Gen Z's values and psychological motivations.